Optimization and Characterization of Syzygium cumini Leaves Extract Alginate–Kappa-Carrageenan Microspheres - Reski Mulia; Meiliza Ekayanti; Mochamad Fajar Deliaz (Indonesian Journal of Pharmaceutical Education, 2026)
Syzygium cumini leaves contain flavonoids and other phytochemicals with promising pharmaceutical potential; however, the direct use of the extract is limited by poor stability and low bioavailability. This study aimed to formulate and characterize alginate–kappa-carrageenan microspheres containing the ethanol extract of S. cumini leaves prepared by ionic gelation using CaCl₂ as a crosslinking agent. The extract was obtained by maceration with 96% ethanol, yielding 19.6%. Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, tannins, and polyphenols. Three formulations containing 0.2%, 0.3%, and 0.4% extract were prepared and evaluated for organoleptic properties, microsphere yield, morphology, particle size, moisture content, and entrapment efficiency (EE). All formulations produced fine light-green powders with a characteristic herbal odor. Microsphere yield ranged from 92.45 ± 0.52% to 93.96 ± 0.52% and differed significantly among formulations (p 0.05). Particle size ranged from 3.16 ± 0.25 to 3.30 ± 0.00 µm, with polydispersity index values of 0.55–0.58, indicating moderately polydisperse systems. Moisture content remained low, ranging from 3.43 ± 0.86% to 3.81 ± 0.45%. EE increased with extract concentration, and F3 showed the highest value (69.91 ± 1.18%), which differed significantly from the other formulations (p 0.05). These findings indicate that alginate–kappa-carrageenan microspheres are a promising carrier system for S. cumini leaf extract and may improve flavonoid protection. Further studies on release behavior and storage stability are needed to confirm their performance.